Oil and Food Price Before and During Covid-19 Pandemic in Nigeria: a Non-linear ARLD Approach - Yusuf, Muhammad-Bashir Owolabi; Salau, Tunde Jibril; Adeiza, Adams (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
This paper analyzes the relationship between food and oil prices in Nigeria before and during the COVID-19 pandemic, using monthly data from January 2018 to December 2021. The ARDL and NARDL models are applied to estimate the symmetry and asymmetric relationship that exists in food price behavior. The NARDL confirms the presence of asymmetries, and the bound test affirms the co-integration and long-run relationship among the variables. In the long run, there is a significant positive relation between oil price increases and food prices, but the long-run impact of oil price reductions on food prices is not significant. In the short run, only increases in oil prices exert a significant influence on food prices, while decreases in oil prices do not. Furthermore, the COVID-19 period exerts a positive and significant impact on food prices, while COVID-19 cases do not influence food prices in Nigeria.